The Impact of ENT Diseases in Social Life - Galletti, Francesco; Gazia, Francesco; Freni, Francesco; Galletti, Cosimo (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In the past several years, the otorhinolaryngology sector has had a significantimpact on social life. About 10% of the cancers that affect the populationannually concern the head and neck, and each year the guidelines evolve andchange.Emergencies of the otolaryngology sector are among the most common, withnumerous increases in hospitalizations in the ENT department (e.g., bleeding,abscesses, and dyspnoea). Interventions in the election can significantly improvepatients' quality of life and help avoid future complications.Given the importance of the medical and surgical branch of otorhinolaryngology,we want to underline the impact in social life of this important area.